P565First characterization of high-power short-duration radiofrequency ablation with remote magnetic navigation assistance. (18th June 2020) - Caluori, G; Odehnalova, E; Krenek, J; Jadczyk, T; Pesl, M; Pavlova, I; Drazanova, E; Starek, Z
Abstract: Funding Acknowledgements: MEYS- CR (ref#LQ1605 and LM2015062) Background/Introduction High-power short-duration (HPSD) radiofrequency (RF) ablation relies on the application of intense thermal fields for a carefully restricted time, in order to quickly obtain deep but precise lesions that spare the structures surrounding the heart. The approach is still under evaluation across different therapies and catheter technologies. To the present day there is no available characterization of HPSD ablation supported by remote magnetic navigation (RMN). Purpose: To describe the safety issues regarding HPSD ablation in atria and ventricles with RMN systems, while characterizing the thermal lesion size and continuity in an acute closed-chest swine model. Methods: The animal trial was divided in two arms (left ventricular and atrial). 10 female large white pigs (6-month-old weight 55-65 kg) were employed in each arm. Endocardial electroanatomical mapping and ablation were performed with RMN assistance to provide stable contact and flexible maneuvering. The ventricular cohort was divided in 5 power settings (30-40-50-60-70W). Multiple RF applications (10 ca./animal) were delivered until a pop occurred or up to 60s. In the atrial cohort the animals were divided by a combination of power/application time (50W/20s – 70W/10s – 90W/4s). Intracaval right atrial ablation lines and postero-lateral left atrial lines were performed in a point-by-point fashion (ca. 4mm distance). Irrigation rate was 30ml/min. The ventricular lesions were measured via software after 9.4T MRI of fixed hearts. The atrial lesions were measures during pathological examination after explanation. Results: In the ventricular arm, we obtained a safety calibration curve linking the imposed power setting to the maximal time of application. The time before a pop decreased non-linearly from 60s down to 17.69 ± 8.21 s at 70W. No statistically significant differences were observed when comparing lesions depth, width and volume among the selected power settings. In the atrial arm we observed on the post-ablation maps a significant decrease of intracaval lesions (i.e. area with bipolar voltage <1.5mV) width (17.57 ± 1.89 mm for 50W/4s down to 10.16 ± 1.56 mm for 90W/4s). Pericardial, pleural and aortic damages were visible across all the employed settings, with less pronounced alterations for 90W/4s. Transmural lesions were visible both on the right and left atrium, with evident gaps for 50W/20s. Conclusion: The presented work assesses for the first time the safety limits of HPSD ablation on healthy ventricular myocardium. We provide a calibration curve for faster RF ablation with comparable lesion features. Furthermore, we expanded the previously reported application in the atrium adding the benefits of stable controlled contact provided by RMN systems. We highlighted the benefits (e.g. faster, continuous and localized lesion formation) and risks for peripheral structures using HPSD ablation for supraventricular tachycardia interventions.